INFLASI DAN TINGKAT BUNGA TERHADAP HARGA OBLIGASI NEGARA RITEL YANG DITERBITKAN PEMERINTAH - Asih Widajati (Jurnal Keuangan dan Perbankan, 2009)
The purpose of this research was to analyze the influence of the Inflation andinterest rate to bond price, and that research was important for obligation holder. The IndonesianGovernment Bonds used in this research were ORI 001, ORI 002, and ORI 003. The data wascollected from Indonesian Stock Exchange using documentation data collecting techniqueand data pooling. The analysis method used in this research was Path Analysis method. Theresult from t-test showed that statistically inflation did not significantly influence interest rateand SBI interest rate had significantly influenced bond price. The result of f-test inflation andinterest rate had significant effect to bond price at 50.60%. This research gave importantinformation for obligation holder even in stable economy. The increase of inflation rate andthe decrease of interest rate that were followed by the increase of bond price gave positiveinfluence to stock marketer especially for bond investor. For that purpose the bond holdershould keep the bond until it was due.